The jail is everywhere: fighting the new geography of mass incarceration - Norton, Jack; Pelot-Hobbs, Lydia; Schept, Judah Nathan; Gilmore, Ruth Wilson (Verso, 2024)
"Contributions from activists, scholars, and journalists describing the effects of the quiet jail boom in the US and sharing strategies from recent fights against jail construction"--